Preparation and characterization of thin-film Pd–Ag supported membranes for high-temperature applications. (19th October 2015) - Fernandez, E.; Coenen, K.; Helmi, A.; Melendez, J.; Zuñiga, J.; Pacheco Tanaka, D.A.; van Sint Annaland, M.; Gallucci, F.
Abstract: This paper reports the preparation, characterization and stability tests of thin-film Pd–Ag supported membranes for high-temperature fluidized bed membrane reactor applications. Various thin-film supported membranes have been prepared by simultaneous Pd–Ag electroless plating and have been initially sealed with a sealing procedure previously validated for Water gas shift (WGS) application (400 °C). The membranes have been characterized for single gas and mixed gas permeation, and for methane steam and autothermal reforming in a fluidized bed membrane reactor at 550–600 °C using a Ru-based catalyst. In addition, the performance of these membranes was compared to commercial membranes from REB Research & Consulting under the same reaction conditions. The applied sealing showed nitrogen leaks at 600 °C and different sealing approaches were tested solving this problem. Finally, also the long-term stability of the thin-film Pd–Ag supported membrane at 600 °C has been investigated. Highlights: Thin Pd-based membranes for high temperature applications are prepared and tested. The membranes are stable in fluidized bed reactor for SMR and ATR. The membrane flux is higher than literature membranes for the same temperatures. Hydrogen recovery of 30% is achieved with high purity.